Muscles of respiration in professional hockey - Zankovets, V. E. (The Russian Journal of Physical Education and Sport, 2017)
Most sportsmen direct their efforts to different groups of muscles development and don`t pay much attention to muscles of respiration. In this case muscles of respiration become limitative factor for further results improvement. Nowadays many specialists in sport pay attention to muscles of respiration training. It is conditioned by the phenomenon, which was called "metaboreflex of respiration muscles". Its essence is in the fact that muscles of respiration in the state of tiredness cause oxygen decrease in an extremity, brain and heart. Material. Experimental check of an additional inhalation resistance methodology application at the training process of highly-qualified hockey players. Research methods: scientific literature analysis and summarizing, experiment, testing, methods of mathematical statistics. Results. The methodology of respiration muscles purposeful training is created and experimentally checked. The article considers the notion "metaboreflex", describes the importance of respiration muscles for sports activity and gives the results of their purposeful training. Conclusion. The experiment clearly proves a positive influence of purposeful training loads on strength, power and volume of sportsmen`s inhalation.